Current and potential economic costs of Opuntia stricta invasions in Africa - Arne B. R. Witt; Brian W. van Wilgen; Russell M. Wise; Tim Beale; Winnie Nunda; Joe Beeken (Biological Invasions, 2026)

RiskScape: a flexible multi-hazard risk modelling engine - Ryan Paulik; Nick Horspool; Richard Woods; Nick Griffiths; Tim Beale; Christina Magill; Alec Wild; Benjamin Popovich; Glenn Walbran; Russel Garlick (Natural Hazards, 2023)
This paper presents the architecture and features of RiskScape software. RiskScape is an open-source software with a flexible modelling engine for multi-hazard risk analysis. The RiskScape engine implements modeller-defined risk quantification workflows as ‘model pipelines’. Model pipeline steps and functions analyse hazard, exposure, and vulnerability data across different spatio-temporal domains using geoprocessing and spatial sampling operations. The RiskScape engine supports deterministic and probabilistic risk quantification, with several probabilistic-based modes described in this paper. RiskScape advances modelling software for multi-hazard risk analysis through several implementation features. The RiskScape engine operates model pipelines independent of system prescribed model input data classifications or standards. Multiple hazard types, metric intensities, and temporal occurrence information is geometry processed and sampled to create coverage data of simultaneous or sequenced multi-hazard events at object-exposure locations. Escalating multi-hazard event impacts are then determined for object-exposures using scripted conditional or nested statements that apply vulnerability functions in a logical sequence of temporal hazard and impact occurrence. These model features, supported by open geospatial consortium standard geospatial data files and operations, expedite RiskScape for modelling multi-hazard risk at any geographical location or scale.